DEVELOPMENT OF THE FINANCIAL SECURITY OF THE STATE: NEUTRALIZATION OF THREATS - Burkaltseva, Diana; Blazhevich, Oleg; Gabrielyan, Oleg; Savchenko, Lyubov; Skorobogatova, Tatiana; Guk, Olga; Vovk, Ekaterina; Abubakarov, Magomed (Revista Inclusiones, 2019)
In the current conditions of the development of the Russian economy, the issue of the activity of state authorities in neutralizing threats to the financial security of the Russian state is of particular relevance. In this connection, the purpose of the article is to determine the methodology for assessing the level of financial security of the state. The article analyzes theoretical approaches to the financial security of the state, as well as presents economic assessment methods and indicators to determine the level of financial security of the state. The study proposes a system of the main indicators of financial security of the Russian Federation, reflecting the critical points of the financial system and financial relations and consisting of security indicators of the fiscal, credit, banking and monetary systems. The integral indicator of financial security is calculated and a graphic representation of the assessment of the level of financial security of the Russian Federation for 2012-2016 is presented.